Cancer Immunotherapy Using Chimeric Antigen Receptor Expressing T-Cells: Present and Future Needs of Clinical Cancer Centers - Gotti, Manuel; Defrancesco, Irene; D’Angelo, Mario; Basso, Sabrina; Crotto, Luca; Marinelli, Alfredo; Maccalli, Cristina; Iaconianni, Vincenzo (Frontiers in Immunology, 2020)
Chimeric Antigen Receptor-T cells (CAR-T) are considered novel biological agents, designed to selectively attack cancer cells expressing specific antigens, with demonstrated clinical activity in patients affected with relapsed/refractory B-cell malignancies. In consideration of their complexity, the use of CAR-T requires dedicated clinical setting and health care practitioners with expertise in the selection, treatment, and management of toxicities and side effects. Such issue appears particularly important when contextualized in the rapid progress of CAR-T cell treatment, translating into a constant need of updating and evolution. Moreover, the clinical grade manufacturing of CAR-T cells is complex and implies articulated regulatory and organizational aspects. The main goal of this review is to summarize and provide an accurate analysis of the clinical, logistic, and regulatory requirements of CAR-T cell centers. Finally, we describe a new occupational figure called “CAR-T specialist” devoted to the establishment and coordination of the required facilities and regulatory landscape in the context of cancer centers.